Advancing room temperature NO2 gas sensing performance through high-energy mechanical milling of Tin-dichalcogenides - de Oliveira Melquíades, Miécio [UNESP]; de Oliveira, Leonardo Soares; da Silva, Ranilson Angelo [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Elsevier, 2024)
Eco-friendly gas sensing devices with simple architecture, reduced cost, and high performance at room temperature are being sought to replace the traditional metallic oxide materials, aiming to address environmental concerns. Lamellae semiconducting materials have shown promising detection properties for this purpose. Here, we investigated the sensing response of SnS2, Sn(S0.5Se0.5)2, and SnSe2 tin-dichalcogenides prepared by high-energy mechanical milling. High RNO2/Rair response signals, from 102 to 106, for 2–100 ppm of NO2 were observed for temperatures between 30 °C and 300 °C. The materials were not sensitive to CO, while H2 detection could only be observed above 200 °C, implying high NO2 selectivity. Additionally, we investigated the influence of samples suspension in water and isopropanol on grain size and morphology. We found that isopropanol crystallizes amorphous selenium phase dispersed in the Sn-Se system and increase the agglomeration in the Sn(S0.5Se0.5)2 system. Deformed and defective particles were observed regardless the preparation methodology. This unique defect-rich morphology might increase surface reactivity for selective NO2 detection by physisorption, owing a high adsorption/desorption rate at room temperature.
Keywords: Gas sensing materials; High energy ball milling; High performance devices; Physisorption mechanism; Tin-dichalcogenides